Students’ Perception of Online Learning Toward Speaking Ability at English Department of Universitas Negeri Padang - Dwi Rahmatadilla; Yuli Tiarina (Journal of English Language Teaching, 2023)
This research examined students’ perception of online learning through five aspects of speaking ability. The design of the research was descriptive research. To collect data, the researcher employed a questionnaire. The questionnaire is made up of 25 close-ended questions related to online learning toward speaking ability. The researcher used cluster random sampling for selecting the sample. The sample was 30 students from five classes, namely K1, K2, K3, K4, and K5 of 2019 English Language Education at Universitas Negeri Padang. The result of this study revealed that many students positively perceived online learning in terms of speaking ability. The students claimed their perceptions that taking part in the process of learning speaking online can positively improve their vocabulary, grammar, and comprehension skills of speaking. Meanwhile, a few students disagree with online learning as a method of learning speaking. They are not sure that online learning gave a positive effect on the fluency and pronunciation aspects of speaking ability. Therefore, it is possible to conclude that online learning requires greater focus, particularly in terms of speaking skills.Keywords: Students’ Perception, Online Learning, Speaking Ability.